Written vs Spoken Narratives by Indonesian ESL Young Learners: A Case Study - Nicolau, Maria Fe Suganob; Sukamto, Katharina Endriati (Universitas Sanata Dharma, 2018)
This study explores how Indonesian ESL Grade 2 elementary students studying in an international school in Jakarta produce written and spoken narratives. The stimulus material used to obtain the data was a four-panel comic strip with no written text. The findings revealed that both productions follow the basic global structure such as story elements, linearity of the storyline, and coherence. However, the written narratives contextually demonstrated formality while the spoken narratives displayed higher frequencies in using structure of discourse (e.g. hedges, contraction, repair and repetitions) and sentence complexity in T-units. Hedges were used as delaying tactics to allow more time for language processing. The use of contractions was due to the rapid production of language that constraints the ability of the students to produce syntactic richness. Repairs illustrated specificity of the chosen words, while repetition stemmed from the linguistic device like onomatopoeia that demonstrated the creative sides of the students to amplify their thoughts. Apparently, sentence complexity using the T-units demonstrated that the spoken narratives outnumbered the written mode. Nevertheless, it was apparent that the 2 T-units or 3 T-units followed a pattern (e.g. independent clause to independent clause with extension) which was a product of the participantsâ€™ knowledge on spellings and construction of formal and complete sentences. These results may implicate that language educators need to heighten the learnersâ€™ awareness of the unique linguistic features of each mode, to provide a clear understanding on how these modes work best in English language, and to attempt in establishing a balance in structure discourse and sentence complexity in T-units.Keywords: ESL young learners, written and spoken narratives, pattern of differencesÂ